Peningkatan Hard Skill Dan Soft Skill Kelurahan Pamulang Timur Tangerang Selatan Menuju SDM Unggul - Angga Pratama; I Nyoman Marayasa; Suharni Rahayu (Universitas Pamulang, 2024)
Based on the results of observations and discussions with friends, the priority problems facedby learning residents are divided into two aspects, namely: internal aspects and externalaspects. The internal aspect is more likely to arise from the learning residents themselvesbecause of their worries because they do not have skills and abilities in other fields such asnot having a diploma. External aspects of inability to compete with other formal schools andalso compete with other communities. The solution offered or proposed in this PKM activityis in accordance with the problems faced by partners, the solution for the internal aspect is toexplore all the potential that exists in the learning citizens so that they are seen andaccustomed to doing so, then motivate or foster the confidence of all learning residents to dareto appear or take part in every activity especially for self-improvement and External aspectsThe solutions offered to partners are providing entrepreneurial management training,including tips on becoming an entrepreneur, using cellphones, social networks to becomebusiness friends. In the management aspect, according to partner problems, the solutionoffered to partners in this Community Service is to provide assistance and counseling inmanaging a good lifestyle so that they are able to compete in the business world. Based on theproposed solution, the expected target in this PKM is the internal aspect. By completingequality education in Package C and getting a diploma, it indirectly becomes the main capitalfor growing self-confidence, because education is very important in the current era ofglobalization. In addition to participating in training so that other skills or abilities can betrained properly. External aspects After participating in partner training, it is hoped that theywill be able to open new startups with the capital of their cellphones and be able to marketthrough existing social networks. Management aspect, In accordance with the problems facedby partners, solutions are offered to friends In accordance with the problems faced bypartners, solutions are offered to friends.Keywords: